Perceptual Simulation of Vertical Object Movement during Comprehension of Auditory and Audiovisual Text in Children and Adults. Issue 5 (2nd July 2020) - Seger, Benedikt T.; Hauf, Juliane E. K.; Nieding, Gerhild
ABSTRACT: It has been argued that people construct situation models during text reception and that these are analogous, multimodal representations of text grounded in perception and action. On the one hand, abundant evidence has been generated that recipients perceptually simulate features of the situation described in the text. On the other hand, findings indicating that pictures facilitate situation model construction have been explained by assuming a causal link between picture processing, perceptual simulation, and situation model construction. Using a picture verification task, we tested whether 5- to 11 year-old children and adults perceptually simulate vertical object movements during reception of narrative text and whether the presence or absence of pictures during text presentation makes a difference. Our results suggest that both children and adults perceptually simulate vertical object movements. In our work, perceptual simulation was not influenced by pictures, so there is no evidence that it mediates the facilitating effect of pictures on situation model construction.